Soft Skill Development in Ophthalmology and its Importance to Aspiring Canadian Medical Students - Carter William Lim; Cindy M.L. Hutnik (University of Ottawa Journal of Medicine, 2018)
Soft skills are social and emotional intelligences that facilitate harmonious interpersonal interactions. Soft skills enable physicians to understand and build rapport with patients. Soft skills are increasingly considered crucial physician qualities within surgical specialties, including ophthalmology. Although avenues exist for general soft skill development, medical students may find challenges directing their development to ophthalmic settings due to medical curricula’s limited ophthalmology exposure. This perspective commentary discusses resources to aid ophthalmic soft skill development. Lectures provide foundational knowledge. Electives and volunteering provide opportunities to practice soft skills. Electives and mentorship direct soft skills towards desired disciplines. Studying and participating in research that utilizes patient-centred outcomes improves current and future care.